2011
DOI: 10.3989/egeol.40422.143
|View full text |Cite
|
Sign up to set email alerts
|

Équidos y Gonfoterios del Pleistoceno tardío de San Pedro, provincia de Buenos Aires, Argentina

Abstract: IntroducciónLos registros de équidos y gonfoterios en el cuaternario de la provincia de Buenos Aires son relativamente frecuentes. Muchos de estos hallazgos han sido de suma utilidad para reconocer secuencias estratigráficas portadoras de mamíferos que constituyen la escala cronológica del Cuaternario en la región (Cione et al., 2007). Durante la década de 1990, estudios bioestratigráficos muy detallados permitieron postular que en la región Pampeana se sucedieron notables cambios en la distribución de los mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
7
0
9
Order By: Relevance
“…As an exception, Tympanoctomys is recorded in the Early Pleistocene (Ameghino 1889;Verzi et al 2002); in addition, Ameghino (1891) reported presence of Aconaemys in the "Pampeano inferior" (Pleistocene) of Córdoba based on mandibular remains and isolated teeth-these specimens being currently missing from the paleontological MACN collection. There is a rich record of Late Miocene-Pliocene extinct octodontids from fossil beds in western Argentina (Rovereto 1914;Marshall and Patterson 1981;Prado et al 1998;Ortiz et al 2012;Esteban et al 2014Esteban et al , 2019Chiesa et al 2019aChiesa et al , 2019bNasif et al 2019;Prevosti et al 2019) that represent the proto-Monte Biome where crown octodontids are assumed to have originated, and where at least part of the genera are currently distributed (Mares 1975;Verzi 2001;Ojeda et al 2013Ojeda et al , 2015. The rationale for absence of species belonging to living genera in these Late Miocene-Pliocene deposits is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As an exception, Tympanoctomys is recorded in the Early Pleistocene (Ameghino 1889;Verzi et al 2002); in addition, Ameghino (1891) reported presence of Aconaemys in the "Pampeano inferior" (Pleistocene) of Córdoba based on mandibular remains and isolated teeth-these specimens being currently missing from the paleontological MACN collection. There is a rich record of Late Miocene-Pliocene extinct octodontids from fossil beds in western Argentina (Rovereto 1914;Marshall and Patterson 1981;Prado et al 1998;Ortiz et al 2012;Esteban et al 2014Esteban et al , 2019Chiesa et al 2019aChiesa et al , 2019bNasif et al 2019;Prevosti et al 2019) that represent the proto-Monte Biome where crown octodontids are assumed to have originated, and where at least part of the genera are currently distributed (Mares 1975;Verzi 2001;Ojeda et al 2013Ojeda et al , 2015. The rationale for absence of species belonging to living genera in these Late Miocene-Pliocene deposits is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For determination of the remains we used morphological characters of the upper molars (P3-4 and M1). However, for morphometric and comparative analysis, we used the remains from other South American horses described by Prado & Alberdi (1994, 2008, 2012, Alberdi & Frassinetti (2000), Alberdi et al (2003), Alberdi & Prado (2004), Prado et al (2005), andRincón et al (2006). Because we only have upper teeth we have used their dimensions on the surface and at 1 cm from it base (length and width) and length of the protocone in surface, to elaborate a multivariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Since this publication, notes and articles proliferated, which in most cases do not reflect the global diversity of this group. The recent papers of Equidae in South America (Alberdi, 1987;Alberdi & Prado, 1992, 1993Prado & Alberdi, 1994, 2012Alberdi et al, 1989Alberdi et al, , 2001aAlberdi et al, , b, 2003Prado et al, 1987Prado et al, , 1998Prado et al, , 2000Prado et al, , 2005Prado et al, , 2013a; among others) distinguish two genera: Equus and Hippidion. Each genus has specific dental morphology, with a clear intraspecific variability.…”
Section: Introductionmentioning
confidence: 99%
“…En el presente estudio se dan a conocer los análisis estadísticos hechos con M3 y m3 del centro-sur de Chile, comparados con datos de Argentina, Bolivia y Brasil (Alberdi et al, , 2007(Alberdi et al, , 2008; Alberdi & Prado, 2011;Frassinetti & Alberdi, 2000Prado et al, 2002Prado et al, , 2012Prado & Alberdi, 2011;Gutiérrez et al, 2005). Lo cual nos permite observar si los molares fósiles analizados se encuentran entre los de mayor tamaño o entre los más pequeños.…”
Section: Introductionunclassified